2017
DOI: 10.1002/cbf.3304
|View full text |Cite
|
Sign up to set email alerts
|

miR‐214 activates TP53 but suppresses the expression of RELA, CTNNB1, and STAT3 in human cervical and colorectal cancer cells

Abstract: High Mobility Group AT-hook 1 (HMGA1) was identified as a target of miR-214 in human cervical and colorectal cancers (CaCx and CRC) in a previous study. While the expression of miR-214 remains suppressed, HMGA1 behaves as a potent oncogene and plays crucial roles in several aberrant signalling pathways by interacting with intermediates like RELA, CTNNB1, STAT3, and TP53 in CaCx and CRC. Hypothetically, miR-214 should be able to regulate the stabilization of some of these intermediates through the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Ectopic overexpression of miR‐214 inhibits cell proliferation and migration of human colon cancer cells. These results are similar to other findings in colon cancer (19, 44, 45). The underlying mechanism of miR‐214 in the progression of colon cancer remains to be clarified.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ectopic overexpression of miR‐214 inhibits cell proliferation and migration of human colon cancer cells. These results are similar to other findings in colon cancer (19, 44, 45). The underlying mechanism of miR‐214 in the progression of colon cancer remains to be clarified.…”
Section: Discussionsupporting
confidence: 93%
“…miR‐214 prohibits cell growth by targeting MELK in hepatocellular carcinoma (18). miR‐214 functions as an antitumor gene and activates TP53 but inhibits the expression levels of RELA, CTNNB1 , and STAT3 in colorectal and cervical cancer cells (19). These controversial data demonstrate that the role of miR‐214 is different depending on its target genes in different cancer types.…”
mentioning
confidence: 99%
“…Increasing researches have demonstrated that miRNAs exert vital roles in various biological process associated with cancer, including cell proliferation, apoptosis, metastasis and chemotherapy-resistant [18][19][20][21]. Substantive investigations reveal that the aberrant levels of miRNAs are strongly linked to the growth and metastasis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a prior study, PlGF could increase the phosphorylation of STAT3 [12]. MiR-214 has been proven to downregulate the expression of STAT3 in human cervical and colorectal cancer cells [29].…”
Section: Discussionmentioning
confidence: 99%